A influência do cosmopolitanismo, afinidade e auto congruência na intenção de visita a destinos internacionais - Saito, Claudio Sunao (2020)
One of the main areas in tourism research, destination choice presents great challenges due to the diversity of factors that affect tourist’s decisions. This dissertation, splinted into three articles, addresses part of this process, investigating the theory related to destination choice and evaluating consumer cosmopolitanism, affinity and, self-congruence constructs that influence the tourist’s intention to visit international destinations. In consumer behavior literature, several studies indicate the influence of these constructs on the intention to buy foreign products, but their influence on the intention to visit international destinations is not clear. This study addresses the subject in the field of tourism, presenting, in the first article, a wide bibliographic review on theme "destinations choice", validating the scale of constructs in the second article and evaluating its influence on the intention to visit an international destination in the third article. Findings from the study indicate that the subject “destination choice” is complex, involving different approaches and theories, the constructs can be used in the tourism area, and there is a positive and significant association between the constructs and visit intention. The influence of cosmopolitanism is greater when considering the mediation exercised by other variables and mainly in situations which tourist has not visited a destination (moderation by the previous visit to destination), in contrast to affinity with the destination, which has a greater influence on intentions of tourists who already visited the destination. Regarding to managerial implications, findings indicate that managers of public and private organizations related to hospitality and tourism should consider, in their decisions, the influence of these constructs in tourist´s decisions, allowing the implementation of actions that enable the connection of tourists with local culture and traditions, generating greater affinity and self-congruence of tourists with destination.